TRANSLATION ERRORS IN ENGLISH-INDONESIAN HUMOR TEXT PRODUCED BY STUDENTS OF BASIC TRANSLATION CLASS - Felicia Gunawan; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2013)
This research aims to help people understand about errors in transferring message in humor text based on Newmark’s Communicative Translation theory. The data is taken from eighty translation texts made by twenty students of Basic Translation Class period 2010/2011 batch 2009. The writer analyzes the translation data and classifies the errors based on the accuracy in transferring the message. The writer wants to find out the kinds of the error and the frequency. The findings are Errors in transferring the message and Possible Variations in Translation.